Determinants of Acute Respiratory Infection (ARI) among Children aged 6-35 months in Indonesia - Qur'aniati, Nuzul; Ni'mah, Lailatun; Putri, Dwi Adven Riana (Universitas Airlangga, 2022)
Introduction: LARC. Acute respiratory infection is a major cause of morbidity and mortality in Indonesia's children aged 6-35 months. Therefore, research on the determinants of acute respiratory infection in children aged 6-35 months needs to be explored to prevent the incidence of acute respiratory infection. This study aimed to analyze the determinants of the incidence of acute respiratory infection in children aged 6-35 months in Indonesia. Methods: This study used the 2017 Indonesian Demographic and Health Survey data with a cross-sectional analytic design. The inclusion criteria were women between the ages of 15 and 49 who had children between the ages of 6 and 35 months and who lived with study participants having symptoms of coughing, rapid breathing, shortness of breath, and chest pain. The sample was 7378 respondents. Data were collected using a questionnaire for women in the 2017 Indonesian Demographic and Health Survey. The data were analyzed using bivariate analysis with a chi-square test and continued with multivariate analysis with binary logistic regression using the STATA application version 14.0 (p-value < 0.05). Results: The incidence of acute respiratory infection in children aged 6-35 months in Indonesia is caused by several factors with significant results including maternal age [AOR=1.33: 95% CI=1.12-1.58], maternal education [AOR=1.35: 95% CI=1.11-1.63 ], wealth quintile [AOR=1.27: 95% CI=1.06-1.53], and exclusive breastfeeding [AOR=1.28: 95% CI=1.04-1.57]. Conculusion: Maternal age, maternal education, wealth quintile, and exclusive breastfeeding contributed to acute respiratory infection among Indonesian children aged 6-35 months in which maternal age is the dominant factor. This study recommends health education on ARI prevention, such as exclusive breastfeeding, ARI prevention, and aid to children, which must be given especially to young, uneducated women.